Cashless society in campus: student's usage and level of awareness / Nurul Azwa Abdul Rais ... [et al.] - Abdul Rais, Nurul Azwa; Mohd Yusop, Noorezatty; Sabtu, Syamila Nabilah; Shamsul Bahrin, Nur Elya Ezzaty (Universiti Teknologi MARA, Kedah, 2022)
The advancement of information technology and the development of digital devices have led to the adoption of cashless payment. In this era, the younger generations have the opportunity to explore and experience cashless transactions earlier than the previous generations. Thus, this paper aims to determine the factors behind the use of cashless transactions among university students and to investigate their level of awareness in information security of this transaction. The findings from a sample of 373 university students in Seremban showed that convenience and speed were the main factors of using cashless payment while ewallet was the most favourable mode of transaction. Meanwhile, students indicated a high level of awareness regarding the threat and risk, privacy and security of software, the risk of using public Wi-Fi, and the use of One- Time Password (OTP) to secure digital payment.